Pengaruh Promosi Penjualan Dan Persepsi Harga Terhadap Kepuasan Pelanggan Dengan Citra Merek Sebagai Variabel Intervening Pada Pengguna Hp Iphone (Studi Kasus Mahasiswa UPI YPTK Padang Khusus Manajemen) - Erik Muhammad Putra; Emil Salim; Engla Desnim Silvia (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to identify and attempt to analyze the effect of sales promotion and price perceptions on customer satisfaction with brand image as an intervening variable for iPhone users (Case Study of UPI YPTK Padang Specialized Management Students). This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this study were UPI YPTK Padang Special Management students. The results of the study found that there is a positive and significant influence between Sales Promotion on Brand Image. There is a positive and significant influence between Perceived Price on Brand Image. There is a positive and significant influence between Sales Promotion on Customer Satisfaction. There is a negative and insignificant effect between Perceived Price on Customer Satisfaction. There is a positive and significant influence between Brand Image on Customer Satisfaction. Brand Image mediates Sales Promotion on Customer Satisfaction. Brand Image mediates Price Perception on Customer Satisfaction.